Designing a Presence Information System for Student Mentoring Activities Using the Laravel Framework - Misna Asqia (The Indonesian Journal of Computer Science, 2024)
STT NF is a private higher education institution that combines technological knowledge with Islamic values. To achieve this goal, STT NF has a program called student mentoring. Mentoring is led by a mentor and attended by several mentees. The mentoring evaluation process is conducted regularly to assess the progress of each mentee in each group. The evaluation results of each group are sent to BKPK of STT NF. The researcher intends to build an information system for student mentoring attendance using Laravel Framework. The design method used the extreme programming approach. Based on the discussions conducted, it determined that there are five mentoring activities dashboards to be created. There are two known user categories, namely admin and mentor. The program was tested using black box testing with 22 scenarios. Based on the testing, it was concluded that all categories function correctly